A lightweight antistatic release film and preparation method thereof
By using the foam aluminum aluminum with loaded copper nano -wire as a filler to build a micro -level structure, the PBT substrate surface can cause the problem that the surface can be high and causes poorly out of the effect. preparation.
Patent Information
- Application Number
- CN202410583593.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-11
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-05-11
AI Technical Summary
In the prior art, the high surface energy of the PBT substrate is not suitable as a raw material for the release film, resulting in poor release effect.
The foam aluminum with a load with low surface energy is used as a filler. It builds a micro -level structure through dopamine modification and eighteen amine modification to reduce the surface energy of the PBT substrate and improve the ionizing effect.
Effectively reduce the surface energy of the PBT substrate, improve the effect of the ionization, overcomes the problem of the traditional iconic membrane easy peeling or grinding loss, and make the ionizing membrane have good anticidarity performance.
Smart Images

Figure BDA0004834802830000061 
Figure BDA0004834802830000071 
Figure BDA0004834802830000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of release films, and in particular to a lightweight antistatic release film and a preparation method thereof. Background Art
[0002] Release film, also known as isolation film, peeling film, separation film, etc. The most commonly used one at present is PET release film, which is a surface treatment of PET substrate, including coating of silicone release agent, fluorine release agent or plasma treatment, so that it has extremely light and stable release force to different organic pressure-sensitive adhesives. This is the most common release film product. The release force of the release film produced is different for the same substrate and different release agents. Polybutylene terephthalate (PBT) is a thermoplastic polyester engineering plastic. It has good mechanical properties, heat resistance and chemical resistance, excellent self-lubricating properties, easy molding and low hygroscopicity. PBT has a fast crystallization speed and can crystallize quickly at a lower temperature, so it has good molding processability and a short molding cycle. In recent years, it has been widely used in industrial fields such as electrical and electronic industries. However, its surface energy is high. From the perspective of the material itself, it is not suitable as a raw material for release film unless it is modified. Therefore, by modifying the PBT film and designing its structure, a release film with good mechanical properties, light weight and good release effect is prepared, which also has great market value. Summary of the invention
[0003] Technical problem to be solved: In view of the above technical problems, the purpose of the present invention is to provide a lightweight antistatic release film and a preparation method thereof, which adopts foamed aluminum loaded with copper nanowires with low surface energy as filler. Due to its own low surface energy, it can reduce the surface energy of the PBT substrate and improve the release effect. At the same time, the foamed aluminum loaded with copper nanowires has a unique structure. The foamed aluminum itself has a micron structure, and both the interior and the surface have nano and micron-level pores. At the same time, it constructs a nano-micro hierarchical structure on the surface of the PBT substrate with the copper nanowires, which further reduces the surface energy, reduces the release force, and improves the release effect.
[0004] Technical solution: A lightweight antistatic release film is obtained by using PBT as a substrate and adding a low surface energy filler; the low surface energy filler is foamed aluminum loaded with copper nanowires having low surface energy.
[0005] Furthermore, the preparation method of the foamed aluminum loaded with copper nanowires having low surface energy is as follows:
[0006] Step 1: Disperse the copper nanowires in a 2 g / L dopamine aqueous solution, adjust the pH of the solution to 8.5 with Tris, disperse by ultrasonic for 25-35 min, and stir magnetically at room temperature for 20-25 h;
[0007] Step 2: vacuum filtration, washing with distilled water until the filtrate is neutral, and drying at 80°C to obtain dopamine-modified copper nanowires;
[0008] Step 3: ultrasonically disperse the dopamine-modified copper nanowires in a 2 g / L dopamine aqueous solution, add aluminum foam particles, adjust the pH of the solution to 8.5 with Tris, and stir at room temperature for 24 h;
[0009] Step 4: washing with distilled water and drying at 80°C to obtain aluminum foam loaded with copper nanowires;
[0010] Step 5: Prepare a 10-15 mM octadecylamine ethanol solution, adjust the pH of the solution to 8.5 with Tris, add the copper nanowire-loaded aluminum foam, and react at 50°C for 48 hours;
[0011] Step 6: After filtering, ultrasonically clean with ethanol and dry.
[0012] Furthermore, the copper nanowire has a diameter of 40-85 nm and a length of 8-15 μm.
[0013] Furthermore, the foam aluminum particles have a particle size of 100-300 μm and a porosity of 90-98%.
[0014] Furthermore, the foamed aluminum particles have nano-scale and micro-scale pores.
[0015] Furthermore, the mass ratio of the dopamine-modified copper nanowires to the foamed aluminum particles is 1:(2-4).
[0016] The method for preparing the above-mentioned lightweight antistatic release film comprises the following steps, measured in parts by weight:
[0017] S1: taking a PBT substrate and placing it in an oven to dry it to obtain a dry PBT substrate;
[0018] S2: Take 500 parts of dry PBT substrate, add 10-30 parts of low surface energy filler, mix well in a high-speed mixer to obtain a mixture;
[0019] S3: placing the mixture in an internal mixer for internal mixing;
[0020] S4: Take out, cool and hot press on a flat vulcanizer at 10 MPa and 220-250°C for 10 min;
[0021] S5: Cool at room temperature for 15 minutes.
[0022] Beneficial effects:
[0023] 1. The present invention adopts aluminum foam loaded with copper nanowires having low surface energy as filler. Due to its own low surface energy, it can reduce the surface energy of the PBT substrate and improve the release effect. At the same time, the aluminum foam loaded with copper nanowires has a unique structure. The aluminum foam itself has a micron structure, and both the interior and the surface have nano and micron-level pores. At the same time, the aluminum foam and the copper nanowires construct a nano-micro hierarchical structure on the surface of the PBT substrate, which further reduces the surface energy, reduces the release force, and improves the release effect.
[0024] 2. The present invention first uses dopamine as an intermediate connector to load copper nanowires on a foam aluminum skeleton to construct a nano (copper nanowires have both micron and nanometer levels) micro (foam aluminum particles) hierarchical structure. At the same time, dopamine can be oxidized and self-polymerized to form polydopamine under a mild environment. A large number of active sites on the surface of polydopamine serve as a secondary reaction platform to modify the low surface energy substance octadecylamine on the foam aluminum particles loaded with copper nanowires to reduce their surface energy.
[0025] 3. The foamed aluminum in the present invention has a small density and a light weight, which can reduce the weight of the overall release film and achieve a light weight effect.
[0026] 4. The foam aluminum and copper nanowires of the present invention are overlapped by two-dimensional and three-dimensional materials, so that good large three-dimensional and small three-dimensional conductive networks can be formed not only between foam aluminum and foam aluminum, between foam aluminum and copper nanowires, and between copper nanowires, thereby improving the conductivity of the material and making the release film have good antistatic effect.
[0027] 5. The low surface energy filler of the present invention can be tightly combined with the PBT substrate, and the release effect can be preserved until the film itself cannot be used, thereby overcoming the disadvantages of the traditional release film that the release agent is coated on the surface, it is easy to peel off or wear and fail, and has a short service life. DETAILED DESCRIPTION
[0028] The present invention proposes a lightweight antistatic release film and a preparation method thereof. In order to make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention will be further described in detail with reference to the embodiments below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0029] Example 1
[0030] The preparation method of aluminum foam loaded with copper nanowires having low surface energy is as follows:
[0031] Step 1: Disperse copper nanowires with a diameter of 40-85 nm and a length of 8-15 μm in a 2 g / L dopamine aqueous solution, adjust the pH of the solution to 8.5 with Tris, and disperse by ultrasonication for 30 min, followed by magnetic stirring at room temperature for 23 h;
[0032] Step 2: vacuum filtration, washing with distilled water until the filtrate is neutral, and drying at 80°C to obtain dopamine-modified copper nanowires;
[0033] Step 3: ultrasonically disperse the dopamine-modified copper nanowires in a 2 g / L dopamine aqueous solution, add aluminum foam particles with a particle size of 100-300 μm and a porosity of 90-98%, adjust the pH of the solution to 8.5 with Tris, and stir at room temperature for 24 hours; the mass ratio of the dopamine-modified copper nanowires to the aluminum foam particles is 1:2;
[0034] Step 4: washing with distilled water and drying at 80°C to obtain aluminum foam loaded with copper nanowires;
[0035] Step 5: Prepare a 13 mM octadecylamine ethanol solution, adjust the pH of the solution to 8.5 with Tris, add the aluminum foam loaded with copper nanowires, and react at 50°C for 48 hours;
[0036] Step 6: After filtering, ultrasonically clean with ethanol and dry.
[0037] Example 2
[0038] The preparation method of aluminum foam loaded with copper nanowires having low surface energy is as follows:
[0039] Step 1: Disperse copper nanowires with a diameter of 40-85 nm and a length of 8-15 μm in a 2 g / L dopamine aqueous solution, adjust the pH of the solution to 8.5 with Tris, and disperse by ultrasonication for 30 min, followed by magnetic stirring at room temperature for 23 h;
[0040] Step 2: vacuum filtration, washing with distilled water until the filtrate is neutral, and drying at 80°C to obtain dopamine-modified copper nanowires;
[0041] Step 3: ultrasonically disperse the dopamine-modified copper nanowires in a 2 g / L dopamine aqueous solution, add aluminum foam particles with a particle size of 100-300 μm and a porosity of 90-98%, adjust the pH of the solution to 8.5 with Tris, and stir at room temperature for 24 hours; the mass ratio of the dopamine-modified copper nanowires to the aluminum foam particles is 1:3;
[0042] Step 4: washing with distilled water and drying at 80°C to obtain aluminum foam loaded with copper nanowires;
[0043] Step 5: Prepare a 13 mM octadecylamine ethanol solution, adjust the pH of the solution to 8.5 with Tris, add the aluminum foam loaded with copper nanowires, and react at 50°C for 48 hours;
[0044] Step 6: After filtering, ultrasonically clean with ethanol and dry.
[0045] Example 3
[0046] The preparation method of aluminum foam loaded with copper nanowires having low surface energy is as follows:
[0047] Step 1: Disperse copper nanowires with a diameter of 40-85 nm and a length of 8-15 μm in a 2 g / L dopamine aqueous solution, adjust the pH of the solution to 8.5 with Tris, and disperse by ultrasonication for 30 min, followed by magnetic stirring at room temperature for 23 h;
[0048] Step 2: vacuum filtration, washing with distilled water until the filtrate is neutral, and drying at 80°C to obtain dopamine-modified copper nanowires;
[0049] Step 3: ultrasonically disperse the dopamine-modified copper nanowires in a 2 g / L dopamine aqueous solution, add aluminum foam particles with a particle size of 100-300 μm and a porosity of 90-98%, adjust the pH of the solution to 8.5 with Tris, and stir at room temperature for 24 hours; the mass ratio of the dopamine-modified copper nanowires to the aluminum foam particles is 1:4;
[0050] Step 4: washing with distilled water and drying at 80°C to obtain aluminum foam loaded with copper nanowires;
[0051] Step 5: Prepare a 13 mM octadecylamine ethanol solution, adjust the pH of the solution to 8.5 with Tris, add the aluminum foam loaded with copper nanowires, and react at 50°C for 48 hours;
[0052] Step 6: After filtering, ultrasonically clean with ethanol and dry.
[0053] Example 4
[0054] The preparation method of aluminum foam loaded with copper nanowires having low surface energy is as follows:
[0055] Step 1: Disperse copper nanowires with a diameter of 40-85 nm and a length of 8-15 μm in a 2 g / L dopamine aqueous solution, adjust the pH of the solution to 8.5 with Tris, and disperse by ultrasonication for 30 min, followed by magnetic stirring at room temperature for 23 h;
[0056] Step 2: vacuum filtration, washing with distilled water until the filtrate is neutral, and drying at 80°C to obtain dopamine-modified copper nanowires;
[0057] Step 3: ultrasonically disperse the dopamine-modified copper nanowires in a 2 g / L dopamine aqueous solution, add aluminum foam particles with a particle size of 100-300 μm and a porosity of 90-98%, adjust the pH of the solution to 8.5 with Tris, and stir at room temperature for 24 hours; the mass ratio of the dopamine-modified copper nanowires to the aluminum foam particles is 1:3;
[0058] Step 4: washing with distilled water and drying at 80°C to obtain aluminum foam loaded with copper nanowires;
[0059] Step 5: Prepare a 10 mM octadecylamine ethanol solution, adjust the pH of the solution to 8.5 with Tris, add the foamed aluminum loaded with copper nanowires, and react at 50°C for 48 hours;
[0060] Step 6: After filtering, ultrasonically clean with ethanol and dry.
[0061] Example 5
[0062] The preparation method of aluminum foam loaded with copper nanowires having low surface energy is as follows:
[0063] Step 1: Disperse copper nanowires with a diameter of 40-85 nm and a length of 8-15 μm in a 2 g / L dopamine aqueous solution, adjust the pH of the solution to 8.5 with Tris, and disperse by ultrasonication for 30 min, followed by magnetic stirring at room temperature for 23 h;
[0064] Step 2: vacuum filtration, washing with distilled water until the filtrate is neutral, and drying at 80°C to obtain dopamine-modified copper nanowires;
[0065] Step 3: ultrasonically disperse the dopamine-modified copper nanowires in a 2 g / L dopamine aqueous solution, add aluminum foam particles with a particle size of 100-300 μm and a porosity of 90-98%, adjust the pH of the solution to 8.5 with Tris, and stir at room temperature for 24 hours; the mass ratio of the dopamine-modified copper nanowires to the aluminum foam particles is 1:3;
[0066] Step 4: washing with distilled water and drying at 80°C to obtain aluminum foam loaded with copper nanowires;
[0067] Step 5: Prepare 11 mM octadecylamine ethanol solution, adjust the pH of the solution to 8.5 with Tris, add aluminum foam loaded with copper nanowires, and react at 50°C for 48 hours;
[0068] Step 6: After filtering, ultrasonically clean with ethanol and dry.
[0069] Example 6
[0070] The preparation method of aluminum foam loaded with copper nanowires having low surface energy is as follows:
[0071] Step 1: Disperse copper nanowires with a diameter of 40-85 nm and a length of 8-15 μm in a 2 g / L dopamine aqueous solution, adjust the pH of the solution to 8.5 with Tris, and disperse by ultrasonication for 30 min, followed by magnetic stirring at room temperature for 23 h;
[0072] Step 2: vacuum filtration, washing with distilled water until the filtrate is neutral, and drying at 80°C to obtain dopamine-modified copper nanowires;
[0073] Step 3: ultrasonically disperse the dopamine-modified copper nanowires in a 2 g / L dopamine aqueous solution, add aluminum foam particles with a particle size of 100-300 μm and a porosity of 90-98%, adjust the pH of the solution to 8.5 with Tris, and stir at room temperature for 24 hours; the mass ratio of the dopamine-modified copper nanowires to the aluminum foam particles is 1:3;
[0074] Step 4: washing with distilled water and drying at 80°C to obtain aluminum foam loaded with copper nanowires;
[0075] Step 5: prepare a 12 mM octadecylamine ethanol solution, adjust the pH of the solution to 8.5 with Tris, add the foamed aluminum loaded with copper nanowires, and react at 50°C for 48 hours;
[0076] Step 6: After filtering, ultrasonically clean with ethanol and dry.
[0077] Example 7
[0078] The preparation method of aluminum foam loaded with copper nanowires having low surface energy is as follows:
[0079] Step 1: Disperse copper nanowires with a diameter of 40-85 nm and a length of 8-15 μm in a 2 g / L dopamine aqueous solution, adjust the pH of the solution to 8.5 with Tris, and disperse by ultrasonication for 30 min, followed by magnetic stirring at room temperature for 23 h;
[0080] Step 2: vacuum filtration, washing with distilled water until the filtrate is neutral, and drying at 80°C to obtain dopamine-modified copper nanowires;
[0081] Step 3: ultrasonically disperse the dopamine-modified copper nanowires in a 2 g / L dopamine aqueous solution, add aluminum foam particles with a particle size of 100-300 μm and a porosity of 90-98%, adjust the pH of the solution to 8.5 with Tris, and stir at room temperature for 24 hours; the mass ratio of the dopamine-modified copper nanowires to the aluminum foam particles is 1:3;
[0082] Step 4: washing with distilled water and drying at 80°C to obtain aluminum foam loaded with copper nanowires;
[0083] Step 5: Prepare a 14 mM octadecylamine ethanol solution, adjust the pH of the solution to 8.5 with Tris, add the foamed aluminum loaded with copper nanowires, and react at 50°C for 48 hours;
[0084] Step 6: After filtering, ultrasonically clean with ethanol and dry.
[0085] Example 8
[0086] The preparation method of aluminum foam loaded with copper nanowires having low surface energy is as follows:
[0087] Step 1: Disperse copper nanowires with a diameter of 40-85 nm and a length of 8-15 μm in a 2 g / L dopamine aqueous solution, adjust the pH of the solution to 8.5 with Tris, and disperse by ultrasonication for 30 min, followed by magnetic stirring at room temperature for 23 h;
[0088] Step 2: vacuum filtration, washing with distilled water until the filtrate is neutral, and drying at 80°C to obtain dopamine-modified copper nanowires;
[0089] Step 3: ultrasonically disperse the dopamine-modified copper nanowires in a 2 g / L dopamine aqueous solution, add aluminum foam particles with a particle size of 100-300 μm and a porosity of 90-98%, adjust the pH of the solution to 8.5 with Tris, and stir at room temperature for 24 hours; the mass ratio of the dopamine-modified copper nanowires to the aluminum foam particles is 1:3;
[0090] Step 4: washing with distilled water and drying at 80°C to obtain aluminum foam loaded with copper nanowires;
[0091] Step 5: Prepare a 15 mM octadecylamine ethanol solution, adjust the pH of the solution to 8.5 with Tris, add the foamed aluminum loaded with copper nanowires, and react at 50°C for 48 hours;
[0092] Step 6: After filtering, ultrasonically clean with ethanol and dry.
[0093] Comparative Example 1
[0094] The difference between this comparative example and Example 2 is that copper nanowires are not loaded, as follows:
[0095] The preparation method of aluminum foam with low surface energy is:
[0096] Step 1: Prepare a 2 g / L dopamine aqueous solution, add foamed aluminum particles with a particle size of 100-300 μm and a porosity of 90-98%, adjust the pH of the solution to 8.5 with Tris, and stir at room temperature for 24 hours;
[0097] Step 4: Wash with distilled water and dry at 80°C to obtain modified aluminum foam;
[0098] Step 5: prepare a 13 mM octadecylamine ethanol solution, adjust the pH of the solution to 8.5 with Tris, add the modified aluminum foam, and react at 50°C for 48 hours;
[0099] Step 6: After filtering, ultrasonically clean with ethanol and dry.
[0100] Various properties of the above examples were measured, including the copper nanowire loading rate and mass-to-volume ratio, and the surface energy was measured with reference to the literature “Pei Ning. Surface modification of brucite and determination of surface energy [D]. College of Materials Science and Engineering, Zhejiang University, 2008.”
[0101]
[0102]
[0103] Taking into account factors such as the copper nanowire loading rate, "lightweight", low surface energy and cost, the aluminum foam loaded with copper nanowires and having low surface energy prepared in Example 2 and Example 7 was selected for subsequent experiments.
[0104] Example 9
[0105] A method for preparing a lightweight antistatic release film, in parts by weight, comprises the following steps:
[0106] S1: taking a PBT substrate and placing it in an oven to dry it to obtain a dry PBT substrate;
[0107] S2: Take 500 parts of the dried PBT substrate, add 10 parts of the foamed aluminum loaded with copper nanowires having low surface energy prepared in Example 2, and mix them evenly in a high-speed mixer to obtain a mixture;
[0108] S3: placing the mixture in an internal mixer for internal mixing;
[0109] S4: Take out, cool and hot press on a flat vulcanizer at 10 MPa and 220-250°C for 10 min;
[0110] S5: Cool at room temperature for 15 minutes.
[0111] Example 10
[0112] A method for preparing a lightweight antistatic release film, in parts by weight, comprises the following steps:
[0113] S1: taking a PBT substrate and placing it in an oven to dry it to obtain a dry PBT substrate;
[0114] S2: Take 500 parts of the dried PBT substrate, add 15 parts of the foamed aluminum loaded with copper nanowires having low surface energy prepared in Example 2, and mix them evenly in a high-speed mixer to obtain a mixture;
[0115] S3: placing the mixture in an internal mixer for internal mixing;
[0116] S4: Take out, cool and hot press on a flat vulcanizer at 10 MPa and 220-250°C for 10 min;
[0117] S5: Cool at room temperature for 15 minutes.
[0118] Embodiment 11
[0119] A method for preparing a lightweight antistatic release film, in parts by weight, comprises the following steps:
[0120] S1: taking a PBT substrate and placing it in an oven to dry it to obtain a dry PBT substrate;
[0121] S2: Take 500 parts of the dried PBT substrate, add 20 parts of the foamed aluminum loaded with copper nanowires having low surface energy prepared in Example 2, and mix them evenly in a high-speed mixer to obtain a mixture;
[0122] S3: placing the mixture in an internal mixer for internal mixing;
[0123] S4: Take out, cool and hot press on a flat vulcanizer at 10 MPa and 220-250°C for 10 min;
[0124] S5: Cool at room temperature for 15 minutes.
[0125] Example 12
[0126] A method for preparing a lightweight antistatic release film, in parts by weight, comprises the following steps:
[0127] S1: taking a PBT substrate and placing it in an oven to dry it to obtain a dry PBT substrate;
[0128] S2: Take 500 parts of the dried PBT substrate, add 25 parts of the foamed aluminum loaded with copper nanowires having low surface energy prepared in Example 2, and mix them evenly in a high-speed mixer to obtain a mixture;
[0129] S3: placing the mixture in an internal mixer for internal mixing;
[0130] S4: Take out, cool and hot press on a flat vulcanizer at 10 MPa and 220-250°C for 10 min;
[0131] S5: Cool at room temperature for 15 minutes.
[0132] Embodiment 13
[0133] A method for preparing a lightweight antistatic release film, in parts by weight, comprises the following steps:
[0134] S1: taking a PBT substrate and placing it in an oven to dry it to obtain a dry PBT substrate;
[0135] S2: Take 500 parts of the dried PBT substrate, add 30 parts of the foamed aluminum loaded with copper nanowires having low surface energy prepared in Example 2, and mix them evenly in a high-speed mixer to obtain a mixture;
[0136] S3: placing the mixture in an internal mixer for internal mixing;
[0137] S4: Take out, cool and hot press on a flat vulcanizer at 10 MPa and 220-250°C for 10 min;
[0138] S5: Cool at room temperature for 15 minutes.
[0139] Embodiment 14
[0140] A method for preparing a lightweight antistatic release film, in parts by weight, comprises the following steps:
[0141] S1: taking a PBT substrate and placing it in an oven to dry it to obtain a dry PBT substrate;
[0142] S2: Take 500 parts of the dried PBT substrate, add 25 parts of the foamed aluminum loaded with copper nanowires having low surface energy prepared in Example 7, and mix them evenly in a high-speed mixer to obtain a mixture;
[0143] S3: placing the mixture in an internal mixer for internal mixing;
[0144] S4: Take out, cool and hot press on a flat vulcanizer at 10 MPa and 220-250°C for 10 min;
[0145] S5: Cool at room temperature for 15 minutes.
[0146] Comparative Example 2
[0147] The difference between this embodiment and embodiment 12 is that the foamed aluminum with low surface energy prepared in comparative example 1 is:
[0148] A method for preparing a lightweight antistatic release film, in parts by weight, comprises the following steps:
[0149] S1: taking a PBT substrate and placing it in an oven to dry it to obtain a dry PBT substrate;
[0150] S2: Take 500 parts of dry PBT substrate, add 25 parts of foamed aluminum with low surface energy prepared in Comparative Example 1, mix them evenly in a high-speed mixer to obtain a mixture;
[0151] S3: placing the mixture in an internal mixer for internal mixing;
[0152] S4: Take out, cool and hot press on a flat vulcanizer at 10 MPa and 220-250°C for 10 min;
[0153] S5: Cool at room temperature for 15 minutes.
[0154] Comparative Example 3
[0155] The difference between this embodiment and comparative example 2 is that an equal amount of copper nanowires as that of embodiment 12 is added separately, specifically:
[0156] A method for preparing a lightweight antistatic release film, in parts by weight, comprises the following steps:
[0157] S1: taking a PBT substrate and placing it in an oven to dry it to obtain a dry PBT substrate;
[0158] S2: Take 500 parts of dry PBT substrate, add foamed aluminum particles and copper nanowires, and mix them evenly in a high-speed mixer to obtain a mixture;
[0159] S3: placing the mixture in an internal mixer for internal mixing;
[0160] S4: Take out, cool and hot press on a flat vulcanizer at 10 MPa and 220-250°C for 10 min;
[0161] S5: Cool at room temperature for 15 minutes.
[0162] The release film prepared in the above embodiment has a thickness of 28 μm and is cut into 1 cm×4 cm strips. The mechanical properties thereof are measured using a universal tensile machine at a loading speed of 2 mm / min and a tensile speed of 5 mm / min.
[0163] The surface energy of the membrane was determined by referring to the literature "Hu Tao. Preparation and protective durability of fluorocarbon nanocomposite coating on hydraulic concrete surface [D]. Yangtze River Scientific Research Institute [2024-05-09]. DOI: CNKI: CDMD: 2.1017.834144."
[0164] The release force of the release film is tested by ASTM D3330 / D3330M-04(2018);
[0165] By measuring its surface resistivity, its antistatic properties were obtained, and the results are shown in Table 1:
[0166] Table 1
[0167]
Claims
1. A lightweight antistatic release film, characterized in that: It is obtained by using PBT as the base material and adding low surface energy fillers; The low surface energy filler is foamed aluminum loaded with copper nanowires having low surface energy; The preparation method of the foamed aluminum loaded with copper nanowires having low surface energy is as follows: Step 1: Disperse the copper nanowires in a 2 g / L dopamine aqueous solution, adjust the pH of the solution to 8.5 with Tris, disperse under ultrasonication for 25-35 min, and then stir magnetically at room temperature for 20-25 h; Step 2: vacuum filtration, washing with distilled water until the filtrate is neutral, and drying at 80°C to obtain dopamine-modified copper nanowires; Step 3: ultrasonically disperse the dopamine-modified copper nanowires in a 2 g / L dopamine aqueous solution, add aluminum foam particles, adjust the pH of the solution to 8.5 with Tris, and stir at room temperature for 24 h; Step 4: washing with distilled water and drying at 80°C to obtain aluminum foam loaded with copper nanowires; Step 5: Prepare a 10-15 mM octadecylamine ethanol solution, adjust the pH of the solution to 8.5 with Tris, add the copper nanowire-loaded aluminum foam, and react at 50°C for 48 h; Step 6: After filtering, ultrasonically clean with ethanol and dry.
2. A lightweight antistatic release film according to claim 1, characterized in that: The copper nanowire has a diameter of 40-85 nm and a length of 8-15 μm.
3. A lightweight antistatic release film according to claim 1, characterized in that: The foam aluminum particles have a particle size of 100-300 μm and a porosity of 90-98%.
4. A lightweight antistatic release film according to claim 1, characterized in that: The mass ratio of the dopamine-modified copper nanowires to the foamed aluminum particles is 1:(2-4).
5. The method for preparing a lightweight antistatic release film according to any one of claims 1 to 4, characterized in that: By weight, the method comprises the following steps: S1: taking a PBT substrate and placing it in an oven to dry it to obtain a dry PBT substrate; S2: Take 500 parts of dry PBT substrate, add 10-30 parts of low surface energy filler, mix well in a high-speed mixer to obtain a mixture; S3: placing the mixture in an internal mixer for internal mixing; S4: Take out, cool and hot press on a flat vulcanizer at 10 MPa and 220-250°C for 10 min; S5: Cool at room temperature for 15 min.
Citation Information
Patent Citations
Low-melting-point PBT electromagnetic shielding composite material and preparation method thereof
CN113621222A
Aluminum-based super-hydrophobic anticorrosive coating and preparation method thereof
CN116334603A